2003
DOI: 10.1002/elan.200302737
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetry and EQCM Investigation of Glutathione Monolayer and Its Complexation with Cu2+

Abstract: The glutathione (GSH) self-assembled monolayer and its compexlation with Cu 2 were studied by using voltammetry and EQCM. It was found that the monolayer could rearrange during the redox process of Cu 2 /Cu . The protonating, or not, of the carboxyl terminates of the adsorpted GSH molecules influence the compexlation interaction significantly for they are the key binding sites. The GSH monolayer had the capacity to accumulate Cu 2 and the monolayer modified gold electrode was employed to detect the low levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 29 publications
(51 reference statements)
2
21
0
Order By: Relevance
“…On the other hand, copper ions have been proven to exhibit electrochemical signals by its complexation with some species, such as GSH [26], polyaspartate [27] and cysteine [28]. This finding is also confirmed by our results.…”
Section: Resultssupporting
confidence: 89%
“…On the other hand, copper ions have been proven to exhibit electrochemical signals by its complexation with some species, such as GSH [26], polyaspartate [27] and cysteine [28]. This finding is also confirmed by our results.…”
Section: Resultssupporting
confidence: 89%
“…Glutathione, which adsorbs readily on gold surfaces [10,11,[30][31][32] is a tripeptide (glutamate-cysteine-glycine) with sulfhydryl group able to form a strong Au-S bond. Different kinds of interparticle interactions between GSH, cysteine and homocysteine have been recently discussed by Maye et al [33].…”
Section: Introductionmentioning
confidence: 99%
“…Gooding and co-workers [42] studied GSH bonded to mercaptopropionic acid as the sensor for Cd(II). The interactions of adsorbed GSH with Cu 2+ have also been studied [31,32]. It has been shown that GSH-SAM's formed on Au piezoelectrodes can act as chemically controlled ion gates [30,[43][44][45][46] and as templates for metal depositions [31].…”
Section: Introductionmentioning
confidence: 99%
“…It can exist in nature in the oxidized (GSSG) and reduced (GSH) forms [34] being the main nonprotein thiol [35] that serves many cellular functions, including maintenance of intracellular redox activities, xenobiotic metabolism, intracellular signal transduction, and gene regulation [36]. Nevertheless, the adsorption of GSH on gold surfaces has been the subject of different studies using a wide range of techniques, such as polarization modulation infrared reflection absorption spectroscopy [37], attenuated total reflection infrared spectroscopy [38], surface enhanced Raman spectroscopy [39], electrochemical quartz crystal nanobalance [40], and cyclic voltammetry [41]. GSH-modified Au surfaces were for example used for specific protein binding processes [42,43].…”
Section: Introductionmentioning
confidence: 99%